From reducing to expanding: a reflexive view on homosexuality - Silva, Gelson Peres da (Revista Hipótese, 2016)
Homosexuals and homosexuality have been treated as minor in the Western society. A review of the meaning[s] of the terms is necessary in order to come from a reducing approach to one that expands the perception of the individuals and their realities. Through defining those terms under analysis and comparing them with the treatment given to heterosexuals in the Western quotidian, and analogies, a new terminology that can provide a fairer portrait of the homosexuals and their various potentials is searched. The cultural evolution within History that has brought others and those nomenclatures and to them meaning[s] which do[es] not correspond to what the universe of the homosexuals comprehends since the upcoming of the term until today, as well as their implications. A new denomination is suggested, and a possibility for others with the purpose of containing the various meanings that constitute homosexuals and that are present in homosexuality.